Supported internships as a vehicle for social inclusion. (22nd October 2021) - Hanson, Jill; Robinson, Deborah; Codina, Geraldene
Accessible summary: A supported internship is a work placement for people with disabilities that includes spending some time at work and some time at school or college. It usually lasts for a year and people get extra support in the work placement. We wanted to find out how supported internships for people with learning disabilities helped them to feel like they belong in workplaces and society. We found that the supported internships we studied did help people with learning disabilities to feel like they belong. The interns developed self‐confidence, they were able to talk to people more easily, and they learned that they were good at things. This was because the people they worked with saw them as individuals who were able to do helpful things. It was also because of the feedback they got at work and how they worked in different departments. We think there should be more supported internships because they help people with learning disabilities to take the next step in life more confidently. Researchers need to find out more about how supported internships can help people to be socially included. Abstract: Background: Obtaining employment for young people with learning disabilities remains challenging, and people may not be able to experience work that offers them the opportunity for broader and deeper social inclusion. Supported internships (SIs) offer a possible solution to this problem, providing a bespoke, structured study programme designed for students with disabilities. Methods: This paper explores, through an ecological systems approach, the experiences of three graduates, six interns, two job coaches and three colleagues, from a long running SI in a large private‐sector organisation that delivers utilities in the midlands in the UK. The organisation has many different departments and interns work in several of these, including the mailroom, reprographics, catering, health and safety, reception, and customer services. The researchers conducted small focus groups and interviews with the participants described above. Findings: Thematic analysis identified three core phenomena of relevance to understanding the relationship between the SI programme and interns' experience of deepened and broadened social inclusion. The first theme illustrated positive changes to interns' and graduates' self‐concept (e.g. self‐determination) and participation, the second captured accounts of reciprocity in relationships, and the third contained insights into the SI practices that were relevant to improved social inclusion. Conclusions: The SI did lead to the broadening and deepening of social inclusion for interns and graduates. The person‐centred ethos of the SI, personalised approaches to workplace adaption and feedback policies were practices that began to emerge as implicated in this impact. Positive developments to self‐concept emerged as important in building interns' and graduates' capacities for participation. The study also demonstrated that an ecological systems approach is useful as a basis for conceptualising and investigating changes to the amount and quality of social inclusion, as experienced by people with learning disabilities.